Kritik Sajak F Rahardi "Nasehat Nenek Pada Cucu Laki-Lakinya yang Sedang Patah Hati" - Dewi Ratnaningsih; Sumarno Sumarno (Edukasi Lingua Sastra, 2021)
Literature criticism could be used as media for connecting the reader and the literature. Stages done in literature criticism is started by interpretation, analysis, and evaluation. Based on interpreation, analysis, and evaluation, this rhyme use clear diction, so it’s become inappropriate for student. In addition, some Indonesian words such as berak, kencing, cebok, and kentut are assumed as inappropriate words. Thus, this literature has low education value for young readers, like students. The use of inappropriate enjambemen also creates and produces unclear meaning in every line of literature.